Communicating Climate Change Oceanically: Sea Level Rise Information Increases Mitigation, Inundation, and Global Warming Acceptance - Velautham, Leela; Ranney, Michael Andrew; Brow, Quinlan S. (Frontiers in Communication, 2019)
Cognitive impediments and global warming’s gradual pace, among other factors, have inhibited some people from detecting climate change’s everyday effects. This results in global warming often being perceived as a non-urgent, non-personal, threat that inhibits larger-scale collective action combatting climate change and public will regarding such action. Extreme weather events that global warming causes or exacerbates (e.g., hurricanes, flooding, heat, and droughts), however, are memorable due to their high emotional, social, and economic costs. Sea level rise is an especially salient American issue, given recent heightened storm surges and the large population-segment who live in or near coastal areas with dangerous flooding risks. In this experiment, we show that providing American participants with U.S-specific information about the economic and/or geographic/cartological effects and risks of sea level rise results in (a) an increased acceptance of oceanic rise as a phenomenon that is concerning and caused by global warming, and (b) an increased acceptance, in general, of global warming’s anthropogenic nature. Communicating sea level rise information also led to (c) a general decrease in nationalism and (d) changes in the perceived effectiveness of mitigation strategies for sea level rise–specifically (d₁) a decrease in the perceived effectiveness of constructing sea walls / dikes and (d₂) an increase in the perceived effectiveness of phasing out fossil fuel usage. Overall, we find that communicating striking information about this oceanic by-product of global warming is an effective way to motivate acceptance and engagement with the issue of climate change in a reasonably broad manner. The experimental findings replicate, extend, and dovetail with prior experiments by our laboratory, bringing up to six the number of brief interventions (i.e., of roughly five or fewer minutes) that have been proven to increase people’s science-normative beliefs about global warming. Our laboratory’s website, HowGlobalWarmingWorks.org, offers samples of these materials, which additionally include surprising statistics, textual and video explanations of global warming’s mechanism, and a contrast of Earth’s temperature rise since the 1880’s versus the U.S. stock market rise since then.